Enlightenment against empire - Muthu, Sankar, 1970- (Princeton University Press, 2003)
In the late eighteenth century, an array of European political thinkers attacked the very foundations of imperialism, arguing passionately that empire-building was not only unworkable, costly, and dangerous, but manifestly unjust. Enlightenment against Empire is the first book devoted to the anti-imperialist political philosophies of an age often regarded as affirming imperial ambitions. Sankar Muthu argues that thinkers such as Denis Diderot, Immanuel Kant, and Johann Gottfried Herder developed an understanding of humans as inherently cultural agents and therefore necessarily diverse.